Acute toxicity is a dose-limiting factor for intravenous polymyxin B: A safety and pharmacokinetic study in healthy Chinese subjects - Liu, Xiaofen; Chen, Yuancheng; Yang, Haijing; Li, Jian; Yu, Jicheng; Yu, Zhenwei; Cao, Guoying; Wu, Xiaojie; Wang, Yu; Wu, Hailan; Fan, Yaxin; Wang, Jingjing; et al. (The Journal of infection, 2021)
•A single-dose (at 0.75 or 1.5 mg/kg) clinical trial of polymyxin B was firstly conducted in healthy Chinese subjects.•Acute toxicity (including neurotoxicity) is a dose-limiting factor for intravenous polymyxin B.•It’s important to monitor the adverse reactions and the polymyxin B daily dose should not exceed 3 mg/kg in general.•Our pharmacokinetic and safety results may benefit the design of Phase I clinical trials for new-generation polymyxins. Polymyxin B is a last-line antibiotic for multidrug-resistant gram-negative bacterial infections. However, limited safety and pharmacokinetic information is available. We investigated the safety and pharmacokinetics of intravenous polymyxin B in healthy subjects. An open-label, single-dose clinical trial was conducted in healthy Chinese subjects. Polymyxin B (sulphate) was administered intravenously at 0.75 or 1.5 mg/kg (n = 10 per dose, 5 males and 5 females) to examine the safety and pharmacokinetics. One female subject in the 1.5-mg/kg group discontinued due to abdominal pain during administration. The most frequently reported adverse events were perioral paraesthesia, dizziness, and numbness of extremities (7/10 subjects in the 0.75-mg/kg group, all subjects in the 1.5-mg/kg group). All neurotoxicity-related events dissipated without treatment within a maximum of 23 h. Notably, abdominal pain (3/5) and vulvar pruritus (2/5), colpitis (2/5) or abnormal uterine bleeding (1/5) were reported in female subjects receiving the 1.5-mg/kg dose. In the 0.75-mg/kg group, the total clearance, volume of distribution and half-life of polymyxin B were 0.028±0.002 L/h/kg, 0.219±0.023 L/kg and 5.44±0.741 h, respectively; similar values were observed in the 1.5-mg/kg group. Urinary recovery was 3.7 ± 1.1% and 8.1 ± 1.3% in the 0.75- and 1.5-mg/kg groups, respectively. Population pharmacokinetics of polymyxin B was consistent with a three-compartment model. The clearance and distribution of the central compartment were 0.027 L/h/kg and 0.071 L/kg, respectively. This study is the first to examine the safety and pharmacokinetics of polymyxin B in healthy subjects. Our results highlight that acute toxicity is a dose-limiting factor for intravenous polymyxin B.